Evaluation of potassium salt of phosphonic acid in Nagpur mandarin with special reference to Phytophthora management - Y V Ingle (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2020)
Phytophthora parasitica var. nicotianae is a major fungal pathogen that causes foot rot, root rot, crown rot, gummosis, leaf fall, and brown rot diseases in Nagpur mandarin in the entire Vidarbha region of Maharashtra. For the efficient management of root rot and gummosis due to Phytophthora, the potassium salt of phosphonic acid (PSPA) was evaluated under field and laboratory conditions. In field trials, infected plants were treated with different concentrations of PSPA by foliar spray and soil drenching. The results revealed that foliar spray + soil drenching of PSPA at 3 ml/liter water was better with respect to the average reduction in no. of lesion with oozing (28.39%), minimum in feeder root index (2.17), increase in canopy volume (11.15%) and higher fruit yield (65.89 kg/ per tree). The effect of PSPA was assayed at three different concentrations against P. nicotianae under in vitro. PSPA was found most effective in arresting the growth of P. nicotianae as complete (100%) inhibition observed in tested doses.